The Effects of Chronic Stress on Migraine Relevant Phenotypes in Male Mice - Kaufmann, Dan; Brennan, K. C. (Frontiers in Cellular Neuroscience, 2018)
Migraine is a disabling neurological disorder affecting 12% of the world’s population. Stress is a major reported trigger and exacerbator of migraine. We evaluated the effects of two chronic stress paradigms on migraine relevant phenotypes in male C57Bl/6 mice. Methods. Fifty six mice were used in a fourteen day social defeat test (SDT) and twenty three mice were used in a forty day chronic variable stress (CVS) paradigm. Anxiety measures were evaluated using the open field and elevated plus maze tests. Migraine relevant phenotypes were evaluated using the nitroglycerin (NTG) and cortical spreading depression (CSD) models. Results. Stress sensitive SDT mice and chronically stressed CVS mice showed decreased exploration in the open field and reduced time spent in the open arms of the elevated plus maze, compared to controls. Stress sensitive SDT mice had increased serum corticosterone levels, and stressed mice in the CVS paradigm had decreased weight gain compared to controls, providing combined behavioral and physiological evidence of a stress response. In the CVS paradigm but not the SDT paradigm, the stressed group showed a significant decrease in baseline mechanical withdrawal threshold compared to controls. SDT and CVS groups as well as controls, showed a significant reduction in withdrawal threshold after treatment with NTG, but the reduction was not larger than in controls. However, stress resistant SDT mice showed a rapid recovery from NTG effects that was not seen in other groups. No difference in CSD frequency was seen between stress and control mice in either stress paradigm. Conclusion. We observed distinct effects of stress on generalized pain response, migraine relevant pain, and migraine relevant excitability. CVS but not SDT was associated with a reduced mechanical withdrawal threshold, consistent with a generalized pain response to chronic stress. Neither SDT nor CVS exacerbated phenotypes considered specifically relevant to migraine - withdrawal to NTG, and susceptibility to CSD. However, the significantly reduced response of stress resilient mice to the NTG stimulus may represent a specific migraine-resistant phenotype.